Singing through struggle: music, worship, and identity in postemancipation Black churches - Hitter Brown, Carolynne (University Press of Mississippi, 2025)
"Singing Through Struggle: Music, Worship, and Identity in Postemancipation Black Churches explores the vital role of music and worship in shaping Black citizenship and identity during Reconstruction. In border cities like Baltimore, Washington, DC, and Philadelphia, churches united newly emancipated migrants and free Black communities, merging identities through cultural negotiation. Music, both a symbol of Black achievement and an expression of identity, became a powerful force in the fight for democracy. Black churchgoers sang together in sanctuaries, homes, schools, and outdoors, using music to resist oppression--uplifting their own ideologies while challenging white supremacy. They infused songs with new meanings that reflected their evolving concerns and struggles. Drawing on fresh archival sources, Singing through Struggle explores the overlooked gap in African American religious music between slavery and the Great Migration, highlighting the continuous stream of Black creativity and dignity that shaped the evolution from spirituals to gospel music. This close study of three Black congregations uncovers forgotten stories of men and women who saw church music as vital to collective purpose and civic identity. Their experiences reveal how faith, music, and ritual helped the Black community navigate a complex, ever-changing reality"--